The effects of interest rates on savings in developing countries - BALASSA, B. (PSL Quarterly Review, 2013)
This paper provides evidence on the effects of interest rates on savings in developing countries. While the evidence is not conclusive, time-series estimates for individual countries as well as cross-section and time-series estimates for a number of countries point to the positive effects of interest rates on savings. At the same time, a variety of factors may have reduced the statistical significance of the estimates. The author points out that estimates of savings in developing countries are subject to considerable error. Also there are other errors associated with the measurement of interest rates and inflation rates, which are necessary to derive real interest rates. Finally, there is evidence that negative real interest rates bring a shift to gold, real estate, and consumer durables, which latter are included in savings as measured in national income statistics. JEL: E43